Brain magnetic resonance imaging and multimodal evoked potentials in benign and secondary progressive multiple sclerosis. Issue 1 (January 1995) - Filippi, M; Campi, A; Mammi, S; Martinelli, V; Locatelli, T; Scotti, G; Amadio, S; Canal, N; Comi, G
Abstract : Brain MRI and multimodal evoked potentials (EPs) were obtained for 13 patients with benign multiple sclerosis and 13 patients with secondary progressive multiple sclerosis, matched for age and duration of the disease, to investigate the nature of the disability in multiple sclerosis. Patients with secondary progressive multiple sclerosis had significantly greater lesion loads for five of seven periventricular regions and for three of nine regions separate from the ventricles. Patients with secondary progressive multiple sclerosis also had more severe infratentorial atrophy scores (p = 0.04), whereas there were no differences between the two groups in number and extent of enhancing lesions. The frequencies were significantly higher and severities greater for multimodal EP abnormalities of all the modalities in patients with secondary progressive multiple sclerosis. At least one EP component was absent in 12 (92%) patients with secondary progressive multiple sclerosis but in only one patient (8%) with benign multiple sclerosis (p < 0.001). There was neurophysiological evidence for cervical cord involvement in eight (61%) patients with secondary progressive multiple sclerosis and in one with benign multiple sclerosis (p < 0.01). These data indicate that the total amount of lesions, the distribution, and the nature of the pathological process might all account for the development of disability in multiple sclerosis.